Analisis Kinerja Keuangan PT. Bumi Resources Tbk - Putri, Dinda Melaty; Ramba, Dina; Rundupadang, Helba (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This research aims to determine the assessment of financial performance in companies. This can be seen in financial reports, namely reports that describe the development of a company's financial results over a certain period of time. The purpose of this research is to find out how the financial performance of PT. Bumi Resources Tbk is based on Liquidity, Solvency and Profitability ratio analysis. The analytical method used is a descriptive quantitative method. Based on the Liquidity ratio, it is in good condition, although it experienced a decline in 2020-2021. Based on the Solvency ratio, the company is in good condition. Based on the profitability ratio, the company's net profit increases, but the company is less effective in using its assets.